Analysis of the Report Card Information System at Aisyiyah Busthanul Athfal Jatibarang Kindergarten - Hilmi, Afafa; Widjatmojo, Galih (Universitas Mohammad Husni Thamrin, 2025)
Early childhood education (PAUD) is an important stage in a child's development because it becomes the foundation for learning at the next level. In the context of education in Indonesia, Kindergarten (TK) has a strategic role in forming a strategic role in shaping a child's cognitive, social and emotional aspects. Aisyiyah Busthanul Athfal Kindergarten (ABA Kindergarten) located on Jl. Tegalwulung, Jatibarang Village, Jatibarang District, Brebes Regency, currently still uses conventional methods in recording children's daily development. Every month, the development data is summarized and retyped conventionally using Microsoft Word to be made into a report or report card. This process is not only time-consuming, but also prone to human error, especially because the filling is done descriptively and differently for each child. In addition, the limited human resources (HR) who understand the use of computers is a challenge in accelerating and simplifying the process of preparing report cards. This study aims to analyze the current system using observation methods, interviews, library research studies, and questionnaire distribution. The analysis was conducted through a survey of the current system, identification of weaknesses, and gathering information needs. Based on the findings of this analysis, further research will design a website-based report card information system that is expected to improve the efficiency and accuracy of descriptive report card preparation. This system will help teachers manage child development data in a structured, timely, and error-free manner.